1992
DOI: 10.1128/aem.58.12.4032-4037.1992
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of NADP-dependent glutamate dehydrogenase from Ruminococcus flavefaciens FD-1

Abstract: Glutamate dehydrogenase (GDH) (L-glutamate:NADP+ oxidoreductase, deaminating, EC 1.4.1.4) from the cellulolytic ruminal bacterium Ruminococcus flavefaciens has been purified and characterized. The native enzyme and subunit are 280 and 48 kDa, respectively, suggesting that the native enzyme is a hexamer. The enzyme requires 0.5 M KCI for optimal activity and has a pH optimum of 6.9 to 7.0. The Kms for ammonia, at-ketoglutarate, and glutamate are 19, 0.41, and 62 mM, respectively. The sigmoidal NADPH saturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Curtis and coworkers purified the native GDH molecule (42) and determined by gel filtration chromatography that the molecular mass was approximately 300,000 Da (7a). This is consistent with the reported molecular masses of other hexameric GDH enzymes (12,17). With few exceptions, the subunit protein of the hexameric enzyme is in the range of 45 to 50 kDa.…”
Section: Gingivalissupporting
confidence: 90%
“…Curtis and coworkers purified the native GDH molecule (42) and determined by gel filtration chromatography that the molecular mass was approximately 300,000 Da (7a). This is consistent with the reported molecular masses of other hexameric GDH enzymes (12,17). With few exceptions, the subunit protein of the hexameric enzyme is in the range of 45 to 50 kDa.…”
Section: Gingivalissupporting
confidence: 90%
“…The cloned enzyme had optimal activity at pH 7.0 (data not shown), again similar to the bacterial enzymes (e.g. [28]). High K + concentrations, up to 0.45 M, had no influence on activity.…”
Section: Biochemical Properties Of the Clonesupporting
confidence: 64%
“…High K + concentrations, up to 0.45 M, had no influence on activity. Wen and Morrison [18] and Duncan et al [28] found requirements for high K + ion concentrations in ruminal bacterial GDHs.…”
Section: Biochemical Properties Of the Clonementioning
confidence: 99%
“…Either in pure culture or in the rumen, ammonia is a preferred inorganic nitrogen source for many ruminal species including S. ruminantium D (Bryant and Robinson 1962;Karsli and Russell 2002) with glutamate dehydrogenase (GDH) and glutamine synthetase (GS) being the primary enzymes involved in ammonia assimilation (Smith et al 1981;Patterson and Hespell 1985;Duncan et al 1992;Woods and Reid 1993;Wen and Morrison 1997;Leigh and Dodsworth 2007). In contrast to other Gram-negative bacteria, S. ruminantium do not exhibit covalent modification of GS for rapid shutdown of this enzyme (Smith et al 1981;Kustu et al 1984).…”
Section: Introductionmentioning
confidence: 99%